2020
DOI: 10.1155/2020/8087273
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Nanoscale Study of Organomineral Complexes of Termite Mounds and Associated Soils: A Systematic Review

Abstract: Termite mounds are replete with natural nanoparticles, and they vary in physicochemical, geochemical, mineralogical, and biological properties from the adjoining soils. Although termite mounds have wide ecological and environmental roles including soil formation, faunal and vegetation growth and diversity, organic matter decomposition, geochemical exploration, water survey, treatment of underground contamination, thermoregulation, gas exchange, and global climate change, their nanoscale structures made by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Clay deposits in Nigeria occupy an estimated 1 billion tons of proven reserves which are available in the nation's states. Previous studies found that, when subjected to refractory tests, the action of termite clay-based materials was in strong contrast with the firebricks obtained (Legese et al, 2021;Eze et al, 2020).…”
Section: Introductionmentioning
confidence: 89%
“…Clay deposits in Nigeria occupy an estimated 1 billion tons of proven reserves which are available in the nation's states. Previous studies found that, when subjected to refractory tests, the action of termite clay-based materials was in strong contrast with the firebricks obtained (Legese et al, 2021;Eze et al, 2020).…”
Section: Introductionmentioning
confidence: 89%
“…Termite mounds are structures of soil built by termites in several tropical ecosystems ( Jouquet et al, 2015 ). These biogenic structures are built to protect the colonies from various environmental and biological factors ( Eze et al, 2020 ). These structures contain soil particles of clay and organic matter cemented together ( Harit et al, 2017 ; Jouquet et al, 2021 , 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the southern and western parts of Ethiopia, the average mound abundance was found to be 12 mound hills/ha, and the estimated termite mound soil mass is 58.9 t/ha (tonne/hectare) (Fufa, 2016). Termite mound soil is available everywhere (Miyagawa et al, 2011;Eze et al, 2020). According to Fuyane et al (2013), extraction of clay for brick making causes land degradation because extensive and excessive clay removal from one place may affect human health by creating pools and still water, which provide a suitable environment for mosquitoes and malaria.…”
Section: Introductionmentioning
confidence: 99%
“…It is a better material than ordinary clay in terms of utilisation for moulding (Alake and Akaninyene, 2014). Globally, it is reported that mounds are clay-rich sites, and the composition of many chemical elements are greater than surrounding soils (Eze et al, 2020).…”
Section: Introductionmentioning
confidence: 99%